Pengaruh Independensi, Kompetensi, Pengalaman, Due Professional Care, Dan Akuntabilitas Terhadap Kualitas Audit ( Studi Empiris Kantor Inspektorat Eks Karisidenan Surakarta ) - Purnamasari, Anik, Dr. Erma Setyawati, Ak., MM (2016)
This research conducted at inspectorate office ex-Surakarta Residence. Thus research due to examine and analyze the influence of independency, competence, experience, due professional care, and accountabillity toward the quality of audit. The populations of this research are all of the apparatus of inspectorate ex-Surakarta Residence which consist of Surakarta, Boyolali, Sukoharjo, Wonogiri, Karanganyar, Klaten, dan Sragen. Total sample of the reseach are 132 respondents determine by purposive sampling. Data analyzes done by classic assumption test and hypothesis testing by double linier regression method. The result of this research shows that the influence of independency, competence, experience, and accountability has impact to the quality of audit. Whereas due professional care has no impact to the quality of audit.